Assessing Dynamic Changes of Taste-Related Primary Metabolism During Ripening of Durian Pulp Using Metabolomic and Transcriptomic Analyses - Sangpong, Lalida; Khaksar, Gholamreza; Pinsorn, Pinnapat; Oikawa, Akira; Sasaki, Ryosuke; Erban, Alexander; Watanabe, Mutsumi; Wangpaiboon, Karan; Tohge, Takayuki; Kopka, Joachim; Hoefgen, Rainer; Saito, Kazuki; et al. (Frontiers in Plant Science, 2021)
Durian is an economically important fruit of Southeast Asia. There is, however, a lack of in-depth information on the alteration of its metabolic networks during ripening. Here, we annotated 94 ripening-associated metabolites from the pulp of durian cv. Monthong fruit at unripe and ripe stages, using capillary electrophoresis- and gas chromatography- time-of-flight mass spectrometry, specifically focusing on taste-related metabolites. During ripening, sucrose content increased. Change in raffinose-family oligosaccharides are reported herein for the first time. The malate and succinate contents increased, while those of citrate, an abundant organic acid, were unchanged. Notably, most amino acids increased, including isoleucine, leucine, and valine, whereas aspartate decreased, and glutamate was unchanged. Furthermore, transcriptomic analysis was performed to analyze the dynamic changes in sugar metabolism, glycolysis, TCA cycle, and amino acid pathways to identify key candidate genes. Taken together, our results elucidate the fundamental taste-related metabolism of durian, which can be exploited to develop durian metabolic and genetic markers in the future.